Microwave-Assisted Synthesis of Carambola-Shaped CuO with Hierarchical Nanostructures - Deng, Chonghai; Hu, Hanmei; Zhang, Xue; Han, Chengliang; Zhao, Difang; Shao, Guoquan (Asian Journal of Chemistry, 2012)
High-quality uniform carambola-shaped CuO with hierarchical nanostructures have been successfully synthesized using Cu(acac)2 and NaOH as starting materials through a convenient microwave heating route. Various techniques have been used to characterize the prepared products, such as X-ray diffraction, field-emission scanning electron microscopy and transmission electron microscopy. The experimental results indicated that the single carambola-shaped nanostructure is a hierarchitecture, which is intersected through the center by two nanoshuttles with thickness of 10-15 nm. The single nanoshuttle (also called as nanostrip bundle) is formed via orderly aggregating of tiny nanostrips with each other through van der Waals force. The morphologies of CuO products were greatly affacted by the concentration of NaOH. The possible reaction process is simply investigated.